2000
DOI: 10.1054/bjoc.2000.1498
|View full text |Cite
|
Sign up to set email alerts
|

A Medical Research Council randomized trial of single agent carboplatin versus etoposide and cisplatin for advanced metastatic seminoma

Abstract: The UK Medical Research Council conducted this trial of carboplatin chemotherapy in advanced seminoma to compare single agent carboplatin with a standard combination of etoposide with cisplatin. The use of single agent carboplatin was expected to be associated with reduced toxicity. A total of 130 patients with advanced seminoma were randomly assigned to treatment with either single agent carboplatin (C) at a dose of 400 mg/m 2 to be corrected for glomerular filtration rate outside the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0
2

Year Published

2001
2001
2012
2012

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 97 publications
(30 citation statements)
references
References 17 publications
0
28
0
2
Order By: Relevance
“…The promising results observed in phase II studies for single agent carboplatin therapy in patients with metastatic seminoma have served as the rationale for two randomised phase III trials conducted in Great Britain and Germany, which compared single agent carboplatin therapy with cisplatin-based combination regimens (Clemm et al, 2000;Horwich et al, 2000). The British trial, however, was prematurely closed due poor accrual and to reports of inferiority of carboplatin-based therapy in patients with metastatic nonseminoma.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The promising results observed in phase II studies for single agent carboplatin therapy in patients with metastatic seminoma have served as the rationale for two randomised phase III trials conducted in Great Britain and Germany, which compared single agent carboplatin therapy with cisplatin-based combination regimens (Clemm et al, 2000;Horwich et al, 2000). The British trial, however, was prematurely closed due poor accrual and to reports of inferiority of carboplatin-based therapy in patients with metastatic nonseminoma.…”
Section: Discussionmentioning
confidence: 99%
“…The British trial, however, was prematurely closed due poor accrual and to reports of inferiority of carboplatin-based therapy in patients with metastatic nonseminoma. The analysis of the 130 seminoma patients randomised until closure of the trial revealed a nonsignificant 10% difference in progression-free and a nonsignificant 5% difference in overall survival in favour of the combination of cisplatin/etoposide (Horwich et al, 2000). The results of the German randomised trial based on 250 patients have demonstrated a statistically significant 21% absolute lower progression-free survival rate following carboplatin therapy compared with the combination of cisplatin, etoposide, and ifosfamide (Clemm et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Patient atteint d'une tumeur germinale sé minomateuse de stade avancé L'analyse a porté sur deux é tudes de qualité mé thodologique critiquable : une é tude ré trospective é valuant la place de la chimiothé rapie (EP ou BEP ou VAB modifié ) par rapport à la radiothé rapie (25 ou 25 Gy + boost de 10 ou 30-45 Gy) chez 128 patients [9] et une analyse poolé e sur donné es individuelles de deux essais randomisé s [11,24] comparant chez 361 patients mé tastatiques une monochimiothé rapie (carboplatine) à une polychimiothé -rapie (VIP ou EP) [7].…”
Section: Chimiothé Rapieunclassified